Estudio del comportamiento visco-elástico de emulsiones inversas concentradas y altamente concentradas a través de un enfoque multiescala (2017)
In this study highly concentrated inverse emulsions (W/O) were characterized by using a multiscale approach. For this, the surfactants Span 80 and Tween 20 were used and the procedures were done with a concentration range of 70-90 (%/w). Likewise, the behavior was measured in macroscopic and molecular scale, at an interfacial level, and the variation of disperse phase concentration over the properties in both scales was studied. Emulsions were characterized in terms of their modules G' and G'' for the macro scale, the interfacial modules G' and G'' and the interfacial tension for the molecular scale. The results showed that elastic response predominates over viscous response in highly concentrated inverse emulsions. Besides, the same behavior was confirmed as in the emulsion and the fluids interface. In addition, it was found that, given an increase in the dispersed phase in the system, there is an increase in the value of G' for the macroscopic and molecular scale.